Audit of Radiology Request Form for Completion and Usefulness of Clinical History: Teaching Hospital Experience, Ghana - Bashiru Babatunde Jimah (Radiology Research and Practice)
Background. The role of the “traditional” radiologist has shifted from imaging centered to patient focus, which underscores the utmost importance of the clinical radiologist in the multidisciplinary team in patient management. For the clinical radiologist to effectively play this key role, the referring clinician must provide adequate and useful patient information to assist the radiologist in making a diagnosis or provide differential diagnosis. The objectives were to assess the level of completion of the radiology request form and to determine whether the clinical history provided aided in the final impression/diagnosis. Materials and Method. We conducted a prospective review of 500 radiology request forms at the Cape Coast Teaching Hospital (CCTH) between September and October 2018. The forms were consecutively sampled and reviewed for each field/area such as patient’s name, age, and clinical history. Data were analyzed descriptively for the level of completeness and usefulness of clinical history entered by the clinician. Results. No request form was completed in full. All the request forms did not have X-ray serial number and previous examination details documented. The proportions of forms with various fields completed were as follows: more than 90% of the forms had patient’s name, investigation required, date of the request, doctor’s name, and clinical history fields filled. The patient’s age, patient’s ward/address, and doctor’s address were filled in 88%, 75%, and 18.4%, respectively. Twenty percent of the request forms were not useful to the radiologist in the final diagnosis. Conclusion. A significant proportion of radiology request forms are incompletely filled and therefore denies the radiologist, the critical information needed to make a diagnosis, or narrow differential diagnosis.